Two New Lytic Bacteriophages of the Myoviridae Family Against Carbapenem-Resistant Acinetobacter baumannii - Zhou, Weilong; Feng, Yu; Zong, Zhiyong (Frontiers in microbiology, 2018)
Two lytic bacteriophages, WCHABP1 and WCHABP12, were recovered from hospital sewage and were able to infect 9 and 12 out of 18 carbapenem-resistant clinical strains, which belonged to different clones. Electron microscopy scan showed that both bacteriophages had the similar morphology as those of the family. Whole genomic sequencing revealed 45.4- or 45.8-kb genome with a 37.6% GC content for WCHABP1 and WCHABP12, both of which showed significant DNA sequence similarity with bacteriophages of the genus within the family. Taxonomic analysis was therefore performed following the proposal approved by the International Committee on Taxonomy of Viruses, which confirmed that WCHABP1 and WCHABP12 represented two new species of the genus. No tRNAs but 88 and 89 open reading frames (ORFs) were predicted for the two bacteriophages, among which 22 and 21 had known function and encoded proteins for morphogenesis, packaging, lysis, and nucleiotide metabolism. The C-terminal amino acids of the large unit of fiber tail proteins varied between the bacteriophages, which may explain their different host ranges. For most lytic bacteriophages, a set of holin and endolysin are required for lysis. However, no known holin-encoding genes were identified in WCHABP1 and WCHABP12, suggesting that they may use alternative, yet-to-be-identified, novel holins for host cell membrane lysis. To test the efficacy of the bacteriophages in protecting against infection, a larva model was used. Only <20% larvae survived at 96 h after being infected by carbapenem-resistant strains, from which the two bacteriophages were recovered. With the administration of WCHABP1 and WCHABP12, the survival of larvae increased to 75%, while the treatment of polymyxin B only slightly increased the survival rate to 25%. The isolation of two new lytic bacteriophages in this study could expand our sight on bacteriophages and may offer new potential therapeutic alternatives against .